Pengaruh Social Media Marketing Terhadap Repurchase Intention Melalui eWOM pada Produk The Originote di Indonesia - Desdia Mulyadi; Fitriani Nur Utami (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Public awareness of skincare is increasing as evidenced by the income from beauty and care products in Indonesia which reached IDR 111.83 trillion. As a skincare brand, The Originote has been able to outperform its competitors through Social media marketing. Social media is a platform for distribution and communication of information between brands and consumers. The role of eWOM in this context is as a strong source of information to find out information from consumers by providing product reviews, recommending or simply sharing experiences. With the Social media marketing and eWOM that have been carried out, it is hoped that it can help the company in growing Repurchase Intention for The Originote products. The aim of this research is to determine the influence of Social media marketing on Repurchase Intention through eWOM. The research method used is a descriptive and quantitative approach. Data collection was through distributing questionnaires and sampling using the probability sampling method in the form of simple random sampling. The sample used in this research was 385 respondents. This research uses SmartPLS version 3 software to process the data. The results of this research found that Social media marketing influences Repurchase Intention, Social media marketing influences Electronic Word of Mouth, Electronic Word of Mouth influences Repurchase Intention and Social media marketing which is mediated by Electronic Word of Mouth influences Repurchase Intention.